(untitled) (International Journal of Studies in Nursing, 2018)
Stunting is a malnutrition condition that caused by long-term insufficient nutrient intake. In 2010, the number of stunting in Indonesia reached 42.38%. In 2013, the prevalence of stunting in Indonesia amounted to 37.2%. The highest occurrence comes from East Nusa Tenggara with more than 50% of the children are stunted. The method used in this paper is Literature Review. We use keyword Risk Factor and Stunting in online resources such as Science Direct, Proquest, PubMed, Google Scholar and another related website. Many risk factors affect stunting in Indonesia. Stunting is caused by multi-dimensional factors and not only caused by malnutrition factors experienced by pregnant women and children under five. Some of the cases described above have contributed to the high prevalence of stunting in Indonesia and therefore a comprehensive intervention plan is required to reduce stunting prevalence in Indonesia.